Evaluation of immune status in patients with breast cancer in Sokoto, Northwestern, Nigeria - M., Bashir B.; H., Yeldu M. (International Journal of Research in Medical Sciences, 2016)
Background: Breast cancer is a major public health problem especially in Sub-Saharan Africa, Nigeria inclusive. It is a leading cause of cancer- related deaths worldwide. The present study assessed the immune status of breast cancer patients using CD4+ T cell count, CD8+ T cell count, CD4+/CD8+ ratio and some leucocytes. Methods: A total of sixty nine (69) subjects that comprised of forty six (46) breast cancer patients attending the Breast Clinic of Usmanu Danfodiyo University Teaching Hospital, Sokoto and twenty three (23) age- and gender-marched apparently healthy individuals as controls were included in the study. Results: The CD4+ T cells (cell/ μl) and CD8+ T cells (cell/ μl) were enumerated using Flow Cytometric method, while CD4/CD8 ratio was calculated from the values obtained from the CD4+ T cells and CD8+ T cells. Even though, there were no significant differences in CD4+ T cells, CD8+ T cells and CD4+/CD8+ ratio based on breast cancer stages and therapy types. Conclusions: It is hereby concluded that, the monocyte counts and CD4+/CD8+ ratio were higher in breast cancer patients and this could be used to differentiate the breast cancer patients from the normal control subjects.